(untitled) (Acta Scientiarum. Biological Sciences, 2011)
The experiment had as objective to study the survival of Piaractus mesopotamicus and Oreochromis niloticus larvae subject to predation by Pantala flavescens larvae with different length classes. We used 120 larvae of P. mesopotamicus, 120 of O. niloticus, and also 24 larvae of Pantala flavescens, distributed in 24 aquariums with useful volume for 2 L, being placed one Odonate for aquarium. The treatments differed as regard to the prey species and the predator size, being kept a control treatment. An aquarium (2 L) containing one larvae of Odonate and 10 larvae of fish were considered an experimental unit. After the beginning, each three hours (18:00, 21:00, 0:00, 3:00, 6:00, 9:00, 12:00, 15:00 and 18:00h), the remnant larvae of fish (alive) in each experimental unit was quantified, and we replaced the consumed larvae, so that we always had 10 larvae of fish at each aquarium after each counting. For both fish species, there was a slight increase in consumption by the Odonate with intermediate size, but the values did not differ statistically (p > 0.05). Larvae of Odonate in the treatments with greater length presented a lower consumption (p < 0.05) than in other treatments.